REGULATORY GAPS AND LEGAL PROTECTION FOR INDONESIAN MIGRANT WORKERS PROFICIENT IN MANDARIN: A Review of Illegal Employment Practices - Kho, Candra; Syarief, Elza; Tan, David (Universitas Islam Negeri Ar-Raniry, 2026)
This study analyzes regulatory gaps and the effectiveness of legal protection for Indonesian Migrant Workers who possess Mandarin language skills and are vulnerable to illegal labor practices. Although Law Number 18 of 2017 establishes a protection framework for the pre-placement, placement, and post-placement stages, its implementation has not fully addressed vulnerabilities arising from informal recruitment, document forgery, and weak oversight of unregistered agencies. Using a normative legal method and a qualitative approach, this research evaluates regulations, employment contracts, BP2MI reports, and studies related to PMI placement in Mandarin-speaking countries. The findings indicate that while Mandarin proficiency can enhance employment opportunities, it also creates loopholes for exploitation, particularly through non-procedural channels that are difficult for consular services and diplomatic protection to reach. Limitations in inter-agency coordination further exacerbate these risks. This study recommends the need for bilateral regulatory harmonization, strengthened oversight based on language competence, enhanced transnational legal aid, and the application of John Rawls principles of justice to reinforce substantial protection for Indonesian Migrant Workers.